2013
DOI: 10.1109/tbme.2012.2228642
|View full text |Cite
|
Sign up to set email alerts
|

The Dual Role of Paramagnetic Particles for Integrated Lysis and Measurement in a Rapid Immunoassay for Intracellular Proteins

Abstract: A novel, integrated lysis and immunoassay methodology and system for intracellular protein measurement are described. The method uses paramagnetic particles both as a lysis agent and assay label resulting in a rapid test requiring minimal operator intervention, the test being homogeneous and completed in less than 10 min. A design study highlights the critical features of the magnetic detection system used to quantify the paramagnetic particles and a novel frequency-locked loop-based magnetometer is presented.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, Sharif et al have recently shown that it is possible to quantify the paramagnetic particles having small magnetic moments by using a properly designed magnetic detection system. 15 Recently, we have demonstrated the high capacity of detecting low concentrations of $10 nm SPIO MNPs and biomolecules tagged to them using a magneto-reactance (MX) based biosensor. 2,7,13 The detection sensitivity of the MX-based biosensor has been reported to reach an extremely high value of 30%, which is about 4 times higher than that of a MI-based biosensor.…”
Section: Introductionmentioning
confidence: 99%
“…However, Sharif et al have recently shown that it is possible to quantify the paramagnetic particles having small magnetic moments by using a properly designed magnetic detection system. 15 Recently, we have demonstrated the high capacity of detecting low concentrations of $10 nm SPIO MNPs and biomolecules tagged to them using a magneto-reactance (MX) based biosensor. 2,7,13 The detection sensitivity of the MX-based biosensor has been reported to reach an extremely high value of 30%, which is about 4 times higher than that of a MI-based biosensor.…”
Section: Introductionmentioning
confidence: 99%